Ethical Issues Associated with Agricultural Biotechnology - Jeff Burkhardt (EDIS)
This is EDIS document FE 347, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published July 2002.